Thermal Stability of Latex Modified Mortars Containing CNTs - Ahmed Abdel-Mohti (International Journal of Concrete Structures and Materials, 2018)
Abstract Durability of concrete and cementitious materials has been of a great concern to the construction industry in the last two decades due to the deterioration of large number of concrete structures which were built in the 60 and 70 s. Among different environmental conditions, the continuous exposure to freeze–thaw and thermal fatigue cycles remains one of the most aggressive conditions to concrete structures and bridges. On the other hand, the use of nanomaterials, such as carbon nanotubes, has shown promising results in improving the properties of cementitious materials. In this paper, the role of using carbon nanotubes (CNTs) in the thermal stability and durability of latex modified mortars (LMM) is examined. CNTs contents of 0.5 wt%, 1.0%, and 1.5 wt% of latex were added prior to mixing the latex modified mortar components and the resulting LMM specimens were subjected to freeze–thaw and thermal fatigue cycles. The mechanical properties and dimensional stability of LMM specimens were then evaluated. In general, it was observed that the addition of CNTs improve the compressive strength of LMM specimens. On the contrary, CNTs have limited or no influence in the tensile strength, development of shrinkage strains, and flexural capacity of LMM specimens under same thermal conditions.